2016
DOI: 10.31478/201605h
|View full text |Cite
|
Sign up to set email alerts
|

Methods for a National Birth Cohort Study

Abstract: This paper is part of the National Academy of Medicine Perspectives series, Lifelong Impact: Why the United States Needs a National Birth Cohort Study. To download both papers in the series, visit www.nam.edu/lifelonghealth. Background: With funding from the Robert Wood Johnson Foundation, the National Academy of Medicine (NAM) and the Division of Behavioral and Social Sciences and Education of the National Academies of Sciences, Engineering, and Medicine held two expert meetings to identify the reason why the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Implementation of the LEnS framework can be accelerated by taking advantage of existing population-based studies. Children’s cohorts with closely linked exposure measurements covering critical windows are ideal for these efforts ( Duncan et al 2016 ). Cross-sectional studies would also be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of the LEnS framework can be accelerated by taking advantage of existing population-based studies. Children’s cohorts with closely linked exposure measurements covering critical windows are ideal for these efforts ( Duncan et al 2016 ). Cross-sectional studies would also be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Restricting sampling and enrollment of women to the first prenatal visit has demonstrated that early pregnancy exposure profiling is possible. The PBS strategy offers the promise of meeting major goals of a longterm birth cohort study in the most efficient manner as is recommended in a recent discussion article by Duncan et al 32 After halting NCS, NIH launched the Environmental Influences on Child Health Outcomes (ECHO) program. 33 Because ECHO was designed to capitalize on existing cohorts with a plan to extend data collection through follow-up visits and/or expand participant populations by recruiting new participants, many of the lessons learned from NCS on sampling strategies will not apply.…”
Section: Figurementioning
confidence: 99%
“…Silicone wristbands are a novel application of passive sampling that O'Connell et al first described in 2014 [18]. Wristbands have been identified as an 'unprecedented measurement platform' that provides individualized chemical exposure data [19], which can be applied to many different types of environmental epidemiological studies [20].…”
mentioning
confidence: 99%